Simultaneous ply-order, ply-number and ply-drop optimization of laminate wind turbine blades using the inverse finite element method. (15th January 2018) - Albanesi, Alejandro; Bre, Facundo; Fachinotti, Victor; Gebhardt, Cristian
Abstract: This paper presents a novel methodology to simultaneously determine the optimal ply-order, ply-number and ply-drop configuration of laminate wind turbine blades using simulation-based optimization, considering the shape that the laminates are expected to attain after large elastic deformations. This methodology combines Genetic Algorithms with the Inverse Finite Element Method. As an actual engineering application, we redesigned the composite stacking layout of a medium-power 40-kW wind turbine blade to reduce its weight, subjected to mechanical and manufacturing constraints such as allowable tip deflection, maximum stress, natural frequencies, and maximum number of successive identical plies. Results demonstrate weight reductions of up to 15% compared to the initial layout, proving that the proposed methodology is a robust redesign tool capable of effectively determining the optimal composite stacking layout of laminate wind turbine blades.